Contralesional angiotensin type 2 receptor activation contributes to recovery in experimental stroke. (September 2022) - Fouda, Abdelrahman Y.; Ahmed, Heba A.; Pillai, Bindu; Kozak, Anna; Hardigan, Trevor; Ergul, Adviye; Fagan, Susan C.; Ishrat, Tauheed
Abstract: We and others have previously shown that angiotensin II receptor type 2 receptor (AT2R) is upregulated in the contralesional hemisphere after stroke in normoglycemic Wistar rats. In this study, we examined the expression of AT2R in type 2 diabetic Goto-Kakizaki (GK) rats and control Wistars after stroke. We also tested the contribution of the contralesional AT2R in recovery after stroke through a specific knockdown of the AT2R in this hemisphere only. Two experiments were conducted. In the first experiment, GK rats were subjected to middle cerebral artery occlusion (MCAO) and treated with the angiotensin II receptor type 1 receptor (AT1R) blocker candesartan or saline at reperfusion. Stroke outcomes, as well as AT2R expression, were examined and compared to control Wistars at 24 h. In the second experiment, localized AT2R knockdown was achieved through intrastriatal injection of short hairpin RNA (shRNA) lentiviral particles or non-targeting control into the left-brain hemisphere of Wistar rats. After 14 days, rats were subjected to right MCAO and treated with the AT2R agonist, Compound 21 (C21), or saline for 7 days. Behavioral outcomes were assessed for up to 10 days. In the first experiment, stroke reduced the expression of AT2R in GK rats. Candesartan treatment failed to improve the neurobehavioral outcomes, preserve vascular integrity or reduce oxidative/nitrative stress or apoptotic markers at 24 h post stroke in these animals. In the second experiment, contralesional AT2R knockdown reduced the C21-mediated functional recovery after stroke. In conclusion, contralesional AT2R upregulation after stroke is blunted in diabetic rats which show reduced sensitivity to post-stroke candesartan treatment. Contralesional AT2R could be involved in C21-mediated functional recovery after stroke. Highlights: Contralesional AT2R upregulation after stroke is blunted in diabetic GK rats. Candesartan treatment failed to improve stroke outcomes in GK rats. Contralesional AT2R knockdown reduced the C21-mediated functional recovery after stroke.